«Project Scope Optimization» software to project scope optimization on terms and cost of its implementation - Кононенко, И. В.; Протасов, И. В.; Мироненко, В. А. (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents the developed software «Project Scope Optimization», that allows to optimize a project scope by time and cost of its implementation if a constraints on the product quality after realization of certain stages are presented. The results of the manual calculation of the test sample using the software are described